2013
DOI: 10.1002/2013wr014213
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐dependence of matrix diffusion in highly heterogeneous rock fractures

Abstract: [1] Diffusive mass transfer in rock fractures is strongly affected by fluid flow in addition to material properties. The flow-dependence of matrix diffusion is quantified by a random variable (''transport resistance'') denoted as b [T/L] and computed from the flow field by following advection trajectories. The numerical methodology for simulating fluid flow is mesh-free, using Fup basis functions. A generic statistical model is used for the transmissivity field, featuring three correlation structures: (i) high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…On the block scale used for a discrete fracture network (DFN) or stochastic continuum conceptualization, we will typically require the flow porosity n f , but also an active specific surface area ω [1/ L ] (Figure b). A m is defined in the usual way for porous media (in this case the rock matrix), whereas ω is pertinent to fractures and depends on the flow; this fact is emphasized by the attribute “active.” For further discussion on the physical meaning of ω , see e.g., Cvetkovic et al (), Cheng et al (), Cvetkovic and Gotovac ().…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the block scale used for a discrete fracture network (DFN) or stochastic continuum conceptualization, we will typically require the flow porosity n f , but also an active specific surface area ω [1/ L ] (Figure b). A m is defined in the usual way for porous media (in this case the rock matrix), whereas ω is pertinent to fractures and depends on the flow; this fact is emphasized by the attribute “active.” For further discussion on the physical meaning of ω , see e.g., Cvetkovic et al (), Cheng et al (), Cvetkovic and Gotovac ().…”
Section: Problem Formulationmentioning
confidence: 99%
“…Statistics of β with ν=1/2 have been studied in 2‐D fractures (Cheng et al, ), in 2‐D DFNs (Frampton & Cvetkovic, ), and in 3‐D DFNs (Cvetkovic & Frampton, ; Makedonska et al, ), as well as analytically (Cvetkovic et al, ). A common simplification is to assume that β is perfectly correlated to τ which writes for the non‐Fickian case as β=ωeff2ν τ [T/L2ν] where ωeff is an effective specific surface area (Cvetkovic & Gotovac, ). The classical Fickian case is obtained with ν=1/2.…”
Section: Applicationsmentioning
confidence: 99%
“…There is unfortunately little field evidence of velocity distribution in bedrock fractures (Cvetkovic and Gotovac, 2013). Shapiro and Hsieh (1998) performed injection tests over short intervals in a crystalline granite/gneiss in central New Hampshire, USA, and found up to 5 orders of magnitude variation in transmissivity.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of single fractures as well as fracture networks have shown that a random variable referred to as ''transport resistance'' (b [T/L]) is required for inferring the SSA of rock fractures [e.g., Cvetkovic et al, 1999;Cvetkovic and Gotovac, 2013]. Theoretical and simulation studies over the past two decades have shed some light on the dependence of the transport resistance on fracture heterogeneity [Cvetkovic, 1991;Moreno and Neretnieks, 1993;Cvetkovic et al, 1999;Cheng et al, 2003;Frampton and Cvetkovic, 2007;Cvetkovic and Frampton, 2012;Larsson et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The flow heterogeneity controls advective transport (Fickian or non-Fickian), but even more significantly controls the SSA. A recent simulation study by Cvetkovic and Gotovac [2013] focuses on residence time and transport resistance in single rock fractures for Gaussian and non-Gaussian transmissivity fields; using these results for a single fracture, we propose here a simple time domain random walk (TDRW) methodology for upscaling of SSA to a network of fractures. The results are compared to discrete fracture network (DFN) simulation results that are based on the most comprehensive field data set currently available [Frampton and Cvetkovic, 2011;Cvetkovic and Frampton, 2012]; even more importantly, the results are compared to the only broad range of SSA estimates from tracer tests reported in the literature Cvetkovic and Frampton, 2010].…”
Section: Introductionmentioning
confidence: 99%